2019
DOI: 10.1029/2018jd029760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sea Surface Roughness and Sea Spray‐Induced Flux Parameterization on the Simulations of a Tropical Cyclone

Abstract: A tropical cyclone (TC) interacts with the ocean through the interchange of surface fluxes of heat and momentum at the air‐sea interface. The sustainability and intensification of TCs are maintained by the enhancement in the latent heat flux in the high wind speed regime. An accurate calculation of heat fluxes is vital to understand the dynamics of the TC. The sea surface roughness is a crucial parameter that modulates the air‐sea fluxes. A coupled ocean‐atmosphere‐wave model is used to simulate TC Vardah over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…COARE is one of the best wind-speed-based z 0 parameterization schemes, which has been widely used in momentum flux calculations [60,61]; the better results from wave-state-based schemes reveal that the characteristics of momentum flux at typhoon condition are better captured by the wave-state-based schemes; this denotes that considering the impacts of wave state can provide more information for the parameterization of z 0 . Similar conclusions are presented by Drennan et al [62] and Prakash et al [63]. From the results of three heat flux parameterization schemes, it is demonstrated that the MSLP results simulated by the ZK scheme are worse than the other two schemes.…”
Section: Track and Intensitysupporting
confidence: 85%
“…COARE is one of the best wind-speed-based z 0 parameterization schemes, which has been widely used in momentum flux calculations [60,61]; the better results from wave-state-based schemes reveal that the characteristics of momentum flux at typhoon condition are better captured by the wave-state-based schemes; this denotes that considering the impacts of wave state can provide more information for the parameterization of z 0 . Similar conclusions are presented by Drennan et al [62] and Prakash et al [63]. From the results of three heat flux parameterization schemes, it is demonstrated that the MSLP results simulated by the ZK scheme are worse than the other two schemes.…”
Section: Track and Intensitysupporting
confidence: 85%
“…New water masses are formed that contain different volumes of the original Atlantic water (Ivanov and Timokhov, 2019). A significant part of the heat content of Atlantic water is spent on melting ice and heating the atmosphere, influencing the climatic characteristics of the region (Rahmstorf and Ganopolski, 1999). To a large extent, the heat exchange between the Barents Sea and the atmosphere is carried out by the turbulent heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…We used the Coupled‐Ocean‐Atmosphere‐Wave‐Sediment Transport (COAWST) modeling system (Warner et al., 2010), which consists of four different components: an atmospheric model (Weather Research Forecasting [WRF], Skamarock et al., 2008), an ocean circulation model (Regional Ocean Modeling System, ROMS, Shchepetkin & McWilliams, 2005), a wave model (Simulating Waves Nearshore, SWAN, Booij et al., 1999), and sediment transport model. The COAWST has been used in a variety of applications such as in studies of atmosphere‐ocean‐wave interactions affected by a hurricane (Olabarrieta et al., 2012; Prakash et al., 2019), wave‐current interactions in the surf zone (Kumar et al., 2012). In this study, the coupled modeling system was used in a coupled WRF‐ROMS mode.…”
Section: Model Description and Experimental Designmentioning
confidence: 99%